VD_FINDINFO HC / 2013 / 409 vom 13. Mai 2013 - VD Tribunal cantonal (2013)
SOCIÉTÉ ANONYME, RAPPORT DE GESTION, RAPPORT DE RÉVISION, ASSEMBLÉE GÉNÉRALE, INFORMATIONEN GÉNÉRAL | 696 CO, 697 CO, 727a al. 4 CO, 731b CO, 308 CPC (CH), 314 al. 1 CPC (CH)